Genetically Modified Food: Health Benefits and Concern - Sameeksha (Indian Journal of Forensic Medicine & Toxicology, 2021)
Genetic Modified Organisms (GMO) are created by manufacturers by introducing genetic material, or DNA, from a different organism through a process called genetic engineering. In most cases the aim is to introduce a new trait to the plant which does not occur naturally in the species like resistance to certain pests, diseases, environmental conditions and herbicides etc. Most currently available GMO foods are plants, such as fruit and vegetables. Existing GM crop includes maize, rice, wheat, soybean, rape, canola, chicory, potato, tomato, cotton etc. GM foods have the potential to solve many of the world’s hunger and malnutrition problems, and to help protect and preserve the environment by increasing yield and reducing reliance upon chemical pesticides. There are many challenges ahead for governments, especially in the areas of safety testing, regulation, industrial policy and food labeling